Go down, Moses - Faulkner, William, 1897-1962. (New York : Vintage International, 1990)
Collection of interrelated stories exploring the complex, changing relations between descendants of the McCaslin clan.
Young Adult
Keywords: Yoknapatawpha County (Imaginary place) -- Fiction; Geographical myths -- Fiction; Short stories; Yoknapatawpha County (Imaginary place) -- Fiction; Southern States -- Social life and customs -- Fiction; Southern States -- Social life and customs -- Fiction